2019
DOI: 10.1186/s13195-019-0544-6
|View full text |Cite
|
Sign up to set email alerts
|

Study partner types and prediction of cognitive performance: implications to preclinical Alzheimer’s trials

Abstract: Background: Alzheimer's disease (AD) clinical trials require enrollment of a participant and a study partner, whose role includes assessing participant cognitive and functional performance. AD trials now investigate early stages of the disease, when participants are not cognitively impaired. This gives rise to the question of whether study partners or participants provide more information in these trials. Methods: We used data from the AD Cooperative Study Prevention Instrument Project (ADCS-PI) to compare par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Discrepancies between participant-and study partner-reported cognitive decline exist on the preclinical and clinical Alzheimer's disease (AD) continuum (Amariglio et al, 2015;Vannini et al, 2017;Nuño et al, 2019;Ryan et al, 2019). However, the longitudinal course of these concerns about cognitive decline remains unclear, particularly with regard to their relationships with brain-based AD biomarkers (i.e., cerebral amyloid and tau protein burden) in the preclinical or prodromal stages of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies between participant-and study partner-reported cognitive decline exist on the preclinical and clinical Alzheimer's disease (AD) continuum (Amariglio et al, 2015;Vannini et al, 2017;Nuño et al, 2019;Ryan et al, 2019). However, the longitudinal course of these concerns about cognitive decline remains unclear, particularly with regard to their relationships with brain-based AD biomarkers (i.e., cerebral amyloid and tau protein burden) in the preclinical or prodromal stages of disease.…”
Section: Introductionmentioning
confidence: 99%
“…By linking the longitudinal trajectories of these concerns with cross-sectional in vivo brain pathology, we may be able to detect and identify cognitive changes earlier in the course of the disease in clinical practice to provide more time for the intervention and treatment. Additionally, whereas most dementia clinical trials require study partners for reasons of consent, compliance, and collection data that the participant is unable to provide, the rationale for the requirement of study partners in preclinical AD trials and ongoing involvement of study partners throughout the study is less clear (Nuño et al, 2019). If longitudinal discrepancies exist between participant and study partner concerns and are linked to biomarker data, this could represent an additional, sensitive outcome measure that is more costeffective and less burdensome to both participants and study staff.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective report of everyday high-level cognitive functioning from both the individual and a close family member or friend, may offer a window into early cognitive changes along the preclinical stage. Indeed, prior studies have shown that both greater cognitive complaints from the participant, as well as from a study partner, are associated with higher likelihood of subsequent cognitive decline and clinical progression (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the AD trials are moving to an earlier disease stage, there is still a suggestion to involve a study partner even in the case of pre-dementia studies [27]. This is despite evidence that accuracy and amount of information provided by study partners may vary [28,29] and the study partner's executive skills may influence the accuracy of subjectively reported ADLs [30] as well as perceived burden on reporting in global assessment scales [31]. Incorporating the individual's own view of well-being is important as there are suggestions individuals in the asymptomatic pre-dementia stages of the AD continuum do experience decline from their own baseline and the combination of biomarker assessments with subjective assessments of subtle change may be useful in this group [32].…”
Section: Discussionmentioning
confidence: 99%